The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.11628/ksppe.2020.23.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Forest therapy program reduces academic and job-seeking stress among college students

Abstract: Background and objective: Recreation or activities in forest are regarded as therapy. Many forest therapy programs have been developed and assessed in the domestic. This study was conducted to investigate the effect of the forest therapy program on academic and job-seeking stress in college students. Methods: Thirty five subjects were selected as the experimental group and 25 as the control group, and 29 subjects in the experimental group and 11 in the control group participated in the follow-up test to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…General characteristics were analyzed with frequency analysis of descriptive statistics, and cross-tabulations are used to test the homogeneity between the groups. In addition, a paired t-test was conducted to determine whether there is statistical significance in the (pretest and posttest) results before and after 11 sessions of the forest therapy program, and the significance level was p < .05 (Kang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…General characteristics were analyzed with frequency analysis of descriptive statistics, and cross-tabulations are used to test the homogeneity between the groups. In addition, a paired t-test was conducted to determine whether there is statistical significance in the (pretest and posttest) results before and after 11 sessions of the forest therapy program, and the significance level was p < .05 (Kang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Noise was a major factor in the selection of sites among several of the guides that we interviewed, and while a few forest therapy studies have measured noise and its effects on health outcomes [39,173,337], the prominence to which it was talked about in our interviews and in the focused studies on tranquility that we reviewed indicate further attention to it is warranted, especially for forest therapy sites near urban areas. Another example relates to the sub-criterion of usable nature, and while our previous forest therapy review paper [22] identified a number of studies where participants engaged in purposeful hands-on stewardship activities [38,338,339] or nature-based arts and crafts activities that made use of forest materials [340][341][342], no studies mentioned the kinds of constraints to active interactions with nature that our guides discussed and our related search of the urban foraging and museumification literature revealed.…”
Section: Reflectionsmentioning
confidence: 99%
“…The forest therapy program duration ranged from finished within 1 day to 10 weeks, with finished within 1 day being the most common among forest therapy programs (n = 7), with more than 1 week having the least frequency (three studies lasting for 8 weeks [38,66,68] and one study lasting for 10 weeks [62]). Among the 17 articles, four conducted follow-up evaluations [41,57,65,66]. The contents of forest therapy programs and control interventions were not exactly the same in different articles.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Other than walking in the forest being performed by all subjects, the forest therapy program intervention methods mentioned most frequently were experiencing the forest through the senses [41,57,[60][61][62][63]65,67,[69][70][71] and meditation in the forest [38,57,60,62,[67][68][69][70]. The interventions taken in studies also included body massages [62,66,67,69], alternately bathing in warm and cold water [67], structured physical activities (e.g., stretching [62,64,68], breathing exercises [41,58,59,65,68], yoga [69], dance [38,66]), nature-based handcrafts [38,61,66,70], and traditional play [62]. In addition, seven of the 17 studies were facilitated by forest therapists or professionals trained with related knowledge [38,62,63,66,68,…”
Section: Study Characteristicsmentioning
confidence: 99%